Development of an Automated Estimating Electronic Weighing Scale - Olalekan OGUNBIYI; Oloruntoba C. MOHAMMED; Lambe Mutalub ADESINA (ABUAD Journal of Engineering Research and Development)
Analog weighing scales suffer from a lack of precision while reading the output and they can easily be manipulated by any technically biased individual. This paper presents the development of an automated estimating electronic weighing indicator. It aims at developing a means to a framework to evaluate estimated weight in analogue to digital forms, such as to obtain higher precision in estimation and calibration. The circuit consists of a Load Cell, Hx711 Load Cell amplifier, Atmega328 microcontroller, LCD module and a few additional glue components. The 20 kg load cell sends signals of the projected loads to the Hx711 module, which magnifies and sends the corresponding output to the microcontroller. The system uses the 4x3 keyboard to input the unit cost per kg to the electronic scale. The microcontroller automatically adjusts the signals with the load cell amplifier module's guide, thus sending the estimated cost in digital form to the LCD module for display. The circuit was designed, constructed, and tested to show that a computerized electronic weighing system can accurately be calibrated without errors.